The social teaching of Jesus Christ: I. The social principles of the teaching of Jesus, II. The social consequences of the teaching of Jesus; two lectures delivered before the University of Pennsylvania, April 22 and 23, 1924 - Peabody, Francis Greenwood (The George Dana Boardman lecturship in Christian ethics, 1924)
The social principles of the teaching of Jesus -- The social consequences of the teaching of Jesus.